Excess intravascular coagulation complicating low cardiac output. Issue 1 (January 1975) - Inglis, T C; Breeze, G R; Stuart, J; Abrams, L D; Roberts, K D
Abstract : In 42 children with congenital heart disease coagulation factor levels were studied serially during the first 20 hours following cardiopulmonary bypass surgery. The acyanotic patients, and also cyanotic patients who survived the operation, showed a progressive improvement in their coagulation profile from initial low postoperative levels. In 12 cyanotic patients who died within 72 hours, however, the coagulation factor levels either remained low, or fell further, until death. Fresh frozen plasma was administered to eight of these patients without apparent benefit. The abnormal coagulation profile correlated significantly with low skin temperature and increased blood loss and was considered to represent excess intravascular coagulation secondary to low cardiac output and poor tissue perfusion.